Complicated left-sided infective endocarditis in chronic hemodialysis patients: a case report - Öykü Gülmez; Mehtap Aydın (KARE Publishing, 2017)
Summary- Infective endocarditis (IE) is a serious infectious condition with high morbidity and mortality in patients with end-stage renal disease (ESRD). It has been particularly associated with recurrent bacteremia due to vascular access via lumen catheters. The most common pathogen is Staphylococcus (S.) aureus, and most affected valve is mitral valve, which frequently calcified. Two patients with ESRD who received hemodialysis treatment via tunneled catheters, aged 56 and 88 years, were admitted with fever and high troponin level. Blood cultures revealed growth of S. aureus. Good quality transthoracic echocardiography (TTE) displayed calcified mitral and aortic valves with no vegetation or abscess formation. Myocardial necrosis as result of catheter infection was considered. Both patients had persistent positive blood cultures 3 and 5 days after initiation of antibiotic treatment. Therefore, transesophageal echocardiogram (TEE) was scheduled. Results revealed perivalvular abscess in the older patient, and highly mobile vegetation in the younger patient. The older patient refused surgery and died soon after due to refractory shock. Mitral valve surgery was planned for the other patient; however, she developed left ventricular failure and bleeding, and also subsequently died as result of refractory shock. Patient evaluations were particularly unfavorable: they had catheter infection as primary focus, and TTE did not detect vegetation or annular abscess. Diagnosis of IE in patients with ESRD using Duke criteria is problematic; we have to keep use of TEE in mind to detect vegetation or abscess formation when there is clinical suspicion regarding ESRD patients even after good quality TTE.